HEARING LOSS RESULTING FROM NOISE EXPOSURE IN TEXTILE WORKERS - F. Akbarkhanzadeh; A. Rezaii; A. Ghiami (Tehran University of Medical Sciences, 1974)
Measurement and analysis of noise level in various frequency bands was carried out in a textile factory. It was shown that the noise level in various working places, particularly in the weaving workshop, was quite excessive comparing to the standards and so, it may very likely result in producing hearing loss in the workers. To determine the hearing loss of the workers due to excessive noise, 136 weavers were randomly selected and examined. However, the number of samples was not large enough to give reliable results. It was concluded that the intensive noise level in the weaving workshops may have produced considerable hearing loss in the workers. Large the exposure to noise, more the hearing loss was observed.